2016
DOI: 10.24200/jeps.vol10iss3pp476-497
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Blended Learning Based on Blackboard in Immediate and Delayed Achievement and Retention in a Physics Course among Health Colleges Students at King Saud University (KSU)

Abstract: Abstract:The study aimed to investigate the effectiveness of blended learning based on the learning management system "Blackboard" in immediate and delayed achievement and retention in a physics course among Health Colleges students at KSU. The study sample consisted of 53 Health Colleges students at KSU, who were divided into two groups: the experimental group (25 students), who studied physics using blended learning based on the Blackboard system; and the control group (28 students), who studied the same con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The present study is compatible with the former studies in the objective; investigating the effectiveness of e-learning in the development of academic achievement (Al-Kandri, 2013;Al-Kadri, 2013;Abdel Aziz, 2014;Al-Materi, 2016;Sawafta & Al Garewai, 2016), study skills (Al-Washahy & Amaar, 2015), and self-confidence (Al-Ghamdi & Afshi, 2017). Previous studies aimed to investigate the effectiveness of blended teaching, based on the e-learning management system "Blackboard", in the development of various variables, such as academic achievement (Al-Kandri, 2013;Al Kadri, 2013;Abdel Aziz, 2014;Al Matari, 2016;Sawafta & Al Garewai, 2016), motivation to e-learning (Al-Kandri, 2013), learning competence (Abdel Aziz, 2014), development of information search skills (Al-Agami,2015), learning retention (Sawafta & Al Garewai, 2016) and motivation to learning (Al-Matari, 2016). The present study matches the former studies concerning the academic level of the participants; university students.…”
Section: Review Of Literaturesupporting
confidence: 88%
See 1 more Smart Citation
“…The present study is compatible with the former studies in the objective; investigating the effectiveness of e-learning in the development of academic achievement (Al-Kandri, 2013;Al-Kadri, 2013;Abdel Aziz, 2014;Al-Materi, 2016;Sawafta & Al Garewai, 2016), study skills (Al-Washahy & Amaar, 2015), and self-confidence (Al-Ghamdi & Afshi, 2017). Previous studies aimed to investigate the effectiveness of blended teaching, based on the e-learning management system "Blackboard", in the development of various variables, such as academic achievement (Al-Kandri, 2013;Al Kadri, 2013;Abdel Aziz, 2014;Al Matari, 2016;Sawafta & Al Garewai, 2016), motivation to e-learning (Al-Kandri, 2013), learning competence (Abdel Aziz, 2014), development of information search skills (Al-Agami,2015), learning retention (Sawafta & Al Garewai, 2016) and motivation to learning (Al-Matari, 2016). The present study matches the former studies concerning the academic level of the participants; university students.…”
Section: Review Of Literaturesupporting
confidence: 88%
“…Results showed statistically significant differences in the cognitive test and card of information search favoring the post-test. Sawafta and Al-Garewai (2016) investigated the effectiveness of blended teaching, based on the e-learning management system "Blackboard", in direct and delayed achievement of physics and learning retention among the students of Health Colleges, King Saud University. The study sample consisted of (53) students divided into two groups; where the experimental group of (25) students studied physics by Blackboard-based blended learning, the control group of (28) ones studied the same course traditionally.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Educators in higher education institutions are now inclined to using technology-driven approaches to course delivery either by prioritizing blended learning in VLEs or fully implementing instruction in the medium of technology-based platforms instead of traditional classroom environments and their respective teaching methods (Al-Khazeem, 2012;Mohsen & Shafeeq, 2014;Sawafta & Al-Garewai, 2016;Hussain, 2016;Al-Ghamdi, 2018;Al-Zahrani & Al-Jraiwi, 2017;Althobaiti & Algethami, 2018;Vo et al, 2017).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Furthermore, McDonald, McPhail, Maguire, and Millett )2004( observed that the increasing application of ICT provides rich learning environments. E-learning is considered to be one of the most important technological contributions to the field of education (Sawaftah & Aljeraiwi, 2016). E-learning is a kind of instruction delivered electronically either through a web browser )using an intranet or the Internet(, or through the use of CD-ROMs or DVD multimedia platforms )Hall, 1997(.…”
Section: Introductionmentioning
confidence: 99%